Women's Agency in Egypt, Jordan, and Tunisia: The Role of Parenthood and Education - Carmen Friedrich; Henriette Engelhardt; Florian Schulz (Population Research and Policy Review, 2020)
Women in Middle Eastern and North African countries continue to report low levels of agency, despite their increasing educational attainment and declining fertility rates. We address this paradox by considering how women's agency is linked to parenthood in Egypt, Jordan, and Tunisia and how this association is moderated by their level of education. We study three dimensions of instrumental agency: involvement in decision-making, financial autonomy, and freedom of movement using data for married women aged 18–49 from the Integrated Labor Market Panel Surveys: Egypt 2012 (n = 7622), Jordan 2016 (n = 4550), Tunisia 2014 (n = 1480). Results from multivariate regression models of these different dimensions demonstrate that married women who are mothers generally exhibit higher levels of agency than their counterparts who are childless, though this does not hold for every dimension and the strength of the association between parenthood and agency differs by dimension and country. We find a notable exception to this pattern of positive association in the Egyptian sample: parenthood decreases agency among Egyptian women with post-secondary education. Our results suggest that parenthood may only increase women's agency in settings with deeply entrenched patriarchal norms that imply little education for women.
Keywords: 300; Women's empowerment; Women's agency; Gender; Parenthood; Middle East and North Africa; Education